Vertical load capacity and quality assessments of bored piles - Arda, Çağdaş. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
There are several methods used in the design of bored piles. To start with, mathematical modeling of the pile and soil parameters provide various formulas and theories for ultimate bearing capacity and settlement calculations of a pile, which are used in pile design. However, such model based analyses seldom give fully reliable results. Many factors, including construction methods and real site conditions also play an important role in the estimation of vertical load capacity. As a result, although economically costly and time-consuming, pile load tests are the most dependable way of measuring the load bearing capacity and displacement behavior of piles. Besides, integrity tests are the most preferable option to check the quality of pile upon installation. Various deep foundation codes have been determined to minimize the risk of foundation failures. These codes recommend higher safety factors for theoretical capacity calculation methods which have a large amount of assumptions and unknowns, whereas lower safety factors for methods which present more detailed and reliable results. However, latter methods are usually more costly and need qualified workmanship. Therefore, for every piling project a cost analysis should be performed which compares the benefit of a method with its disadvantage to decide for the most economic pile design. The main purpose of this thesis is to compare the allowable capacity and displacement values of several load test results with each other and also with theoretical capacity calculations conducted on bored piles in three different case studies consisting of rock sockets in order to decide the most preferable and cost effective design option for each case. The effect of correlations and differences between test results to the design will be investigated, to compare the reliability of a displacement based design with a capacity based design. Besides, integrity test results will also be analysed to underline the effect of construction quality to bored pile capacity.
Keywords: Piling (Civil engineering)